Test, track, treat using wearable sensors for management of Parkinson’s disease: 12‑month prospective observational United Arab Emirates study using Parkinson’s Kinetograph (EmPark-PKG Study) - Metta, Vinod; Qamar, Mubasher A.; Poplawska-Domaszewicz, Karolina; Ibrahim, Huzaifa; Hussain, Hasna; Nalarakettil, Afsal; Tanjung, Gloria; Chaudhuri, K. Ray (Journal of Neural Transmission, 2025)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder marked by both motor and non-motor symptoms that necessitate ongoing clinical evaluation and medication adjustments. Home-based wearable sensor monitoring offers a detailed and continuous record of patient symptoms, potentially enhancing disease management. The EmPark-PKG study aims to evaluate the effectiveness of the Parkinson’s KinetoGraph (PKG), a wearable sensor device, in monitoring and tracking the progression of motor symptoms over 12 months in Emirati and non-Emirati PD patients. Fifty PD patients (32% Emirati, 68% non-Emirati) were assessed at baseline and a 12-month follow-up. Clinical evaluations included levodopa equivalent daily dosage (LEDD) and motor and non-motor assessments. Concurrently, the PKG provided metrics such as bradykinesia score (BKS) and dyskinesia score (DKS). Statistical analyses were conducted to determine changes from baseline to six months, differences between Emirati and non-Emirati groups, and correlations between PKG metrics and clinical assessments. Significant reductions in LEDD and improvements in both motor and non-motor scores were observed from baseline to six months (p < 0.05). PKG-guided medication adjustments were associated with enhanced motor and non-motor outcomes (p < 0.05). Specifically, non-Emirati patients exhibited a significant reduction in LEDD (Z = − 2.010, p = 0.044), whereas Emirati patients did not (Z = − 0.468, p = 0.640). Both groups showed significant improvements in motor scale scores and motor complication scores. Spearman correlation analysis revealed strong relationships between PKG metrics and subjective clinical assessments (p < 0.001). The EmPark-PKG study demonstrates the potential benefits of remote PKG monitoring for personalised motor symptom management in PD. PKG supports a stepped care paradigm by enabling bespoke medication titration based on objective data, facilitating tailored and effective patient care.